PEMASARAN PRODUK BAKERY ROTI DI PONDOK PESANTREN AL- MASHDUQIAH PATOKAN KRAKSAAN - Tri Nadhirotur Roifah; Dewi Pramita (Faculty of Islamic Economics and Business, 2020)
Competition in economic activities is often used to find out how marketing strategies are formed. To establish a marketing strategy by a company, something product can be offered to the market to get attention to be bought, used, or consumed, so that it can meet the wants and needs. In the marketing mix strategy, the first step to take is a product strategy. This is very important because what will be sold is the product and consumers will get to know the company through the products that will be offered. Whereas marketing is marketing, marketing strategy is the design, implementation, and control of plans to influence exchange in order to achieve organizational goals. Strategy is an organizational tool used to achieve its objectives, and therefore, marketing strategy is needed in achieving success.This research is a type of field research (filed research), which is a study by conducting observations about a phenomenon in a scientific situation. While in data collection using, observation, interview, and documentation.The results of this study explain that the Home Industry of Bakery Bread Products use a face to face strategy, a cooperation strategy. And marketing mix which includes product strategy, price, place, promotion. After exposing the marketing of Bakery Bread products, it is expected to activate the stages of product marketing in all places by looking at the conditions of strengths and weaknesses and environmental changes, so that it can find out whether marketing is applied right on target or not. And further enhance the development of the ability of employees to convince the public to trust the industry that has been created by the Al-Mashduqiah Islamic Boarding School, so that the product becomes better and is also well-known among the outside community. Keywords: Marketing, Products, Bakery Bread